DAMPAK KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARTD (IFRS) TERHADAP PERGESERAN PRINSIP SYARIAH (Studi Kasus : PT Bank Muamalat Indonesia Tbk) - Indrawan Azis; Febrina Nur Ramadhani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study entitled Impact of Convergence to International Financial Reporting Standard (IFRS) Shifting Against Sharia, with the purpose of research; (1) the consequences of substance over form to shifts Islamic principles in PT Bank Muamalat Indonesia Tbk., (2) the consequences of the size of the probability of the shift of Islamic principles in PT Bank Muamalat Indonesia Tbk., (3) consequences of the time value of money to the shifting Islamic principles on PT Bank Muamalat Indonesia Tbk. The method used the analysis of rational criticism. The results showed Bank Muamalat Annual Report for 2012 has applied PSAK based IFRS. However, the consequences of convergence is causing a shift in the principles of sharia is a cornerstone in the company's operating system.